TRANSFORMASI PERTUNJUKAN WAYANG BEBER JAKA KEMBANG KUNING MENJADI PERTUNJUKAN TEATER PANGGUNG - nurcahyono, wahid (Tonil: Jurnal Kajian Sastra, Teater dan Sinema, 2017)
Visually traditional Wayang Beber becomes unattractive when compared with the puppet, puppet show, or other stage plays. This is the reason why Wayang Beber need to get a good touch broadly on the form and meaning of the play contained therein. Theatrical action, song and music, color and composition are used as a means of said stories provide a wider opportunity for the emergence of imagination in the audience. The entire string of performances will form a separate text with an open and straightforward meaning. Active role of the viewer is needed in order to create a strong braid between the artist, the copyrighted work as well as the audience. It takes the efforts to invite more radical audience to be part of an artwork intact. Breakthroughs such as involving the viewer to enter into the process or the show can be a separate option in the lifestyles of people who are too lazy to visit the venue. Invites viewers into direct contact with the expected performances more intimate communication. Key word : Wayang Beber, unattractive, intimate communication